THE FULFILLMENT OF THE LAW ACCORDING TO MATTHEW 5:17: A DIALECTICAL APPROACH - P la G du Toit (Acta Theologica, 2018)
In this contribution, the five main views in understanding the fulfilment of the law in Matthew 5:17 are critiqued in terms of their inconsistency with the co-text of the Gospel. The whole of 5:17-48 is assessed in terms of the challenging relationship between the statements about fulfilment or completion of the law and the Prophets in 5:17-18 and the way in which Jesus seems to intensify obedience to law per se in 5:19-48. The interpretation of 5:19-48 is sought by considering all of Jesus’ words in the entire Gospel in terms of entry into the kingdom (5:19-20), doing the perfect will of the Father (5:48), and the way in which the law and the Prophets are fulfilled and accomplished in Christ (5:17-18). A dialectical approach is followed wherein statements concerning the retention of strict obedience to law are considered to be part of the thesis; statements that are opposed to strict obedience to law are considered to form the antithesis, and the way in which these opposites are related is considered as the new synthesis. This thesis, antithesis and synthesis form the solution to understanding fulfilment in Matthew 5:17.